Design-based research as a model for systematic curriculum development: The example of a curriculum for introductory optics - Claudia Haagen-Schützenhöfer (American Physical Society, 2020)
[This paper is part of the Focused Collection on Curriculum Development: Theory into Design.] Although curriculum design has a long tradition in physics education research (PER), it is often criticized for unclear or inconsistent methodologies. One reason is that the theory-into-practice aspect frequently remains blurred. Only a few curriculum projects have given insight into the rule-guided translation of learning theories into curricula and curriculum materials. This paper reports how design-based research (DBR) was used as a framework for systematic curriculum development during a six-year-long project on a middle school optics curriculum. One key feature of DBR is to deduce design principles from theoretical and empirical foundations, apply them in the creation of a curriculum, and refine them in response to data collected during successions of implementation. The design principles guide and structure the iterative cycles of design—intervention—redesign and make a systematic and nevertheless flexible design process transparent. We provide the level of detail needed to make clear how design principles were developed and applied in the creation of the optics curriculum. In addition, we use many examples to illustrate how and why the initial set of design principles was refined. We report the results of a large scale evaluation of the curriculum that shows its superiority to conventional instruction. Finally, we summarize the lessons learned during this project. This shall support other scholars in designing and implementing curricula.